Text. context. edition. (огляд семінару) - Кобиринка, Г. (Iнститут української мови НАН України, 2009)
On February the Institute of Ukraine of Ukrainian NA of Sci. and T.G. Shevchenko Institute of literature Ukrainian NA of Sci. conducted the first meeting of scientific seminar "Text. Context. Edition", the purpose of which was to extend the circle of specialists of different industries of gumanitary, which would estimate text from positions of its polyinformatical state, researches and edition practice were orientated on authenticity of text.